Single domain growth and charge ordering of epitaxial YbFe2O4 films. Issue 35 (13th August 2021) - Sakagami, Takumi; Ota, Reika; Kano, Jun; Ikeda, Naoshi; Fujii, Tatsuo
Abstract : (0001)-Oriented epitaxial YbFe2 O4− δ films without twin domains were formed on YSZ (111) substrates. The charge ordered structure and the large magnetization comparable to bulk single crystals were confirmed on the films. Abstract : YbFe2 O4 is a charge-ordered ferroelectric that exhibits coupling between magnetization and electric polarization near room temperature and crystallizes in a rhombohedral structure ( R 3̄ m ). This study presents an attempt to fabricate stoichiometric and epitaxial YbFe2 O4− δ films with a nearly single-domain structure using an RF magnetron sputtering method. The (0001)-oriented epitaxial films of YbFe2 O4− δ on YSZ (111) substrates via reactive sputtering method exhibited clear three-fold symmetry normal to the substrate without the formation of twin domains rotated by 60°. The oxygen stoichiometry of the epitaxial YbFe2 O4− δ was improved by controlling an oxygen partial pressure ( P O2 ) during the deposition. The films showed a sharp ferrimagnetic transition, and the transition temperature ( T N ) increased linearly to approximately 245 K with decreasing P O2 . The magnitude of magnetization of the obtained films was comparable to that of bulk single crystals. Further, the electron diffraction pattern of the stoichiometric films confirmed the presence of three-dimensional charge order, which is consistent with the behavior of the bulk crystals as well.